Structure-activity relationships for Poly(phenylene)vinylene derivatives as antibacterial agents - Tolosa, Juan (2018)
A series of poly(phenylene)vinylene (PPV) derivatives with different geometries and peripheral functional groups have been synthesized by Horner-Wadsworth-Emmons reaction. Compounds bearing carboxylic acid or quaternary ammonium functional groups prepared by this metal-free protocol were weakly active against both Gram-negative and Gram-positive bacteria, which is in contrast to previously reported results. The activity of polyanionic derivatives was higher for Gram-negative bacteria and showed bacteriostatic behavior, whereas polycationic derivatives were clearly more active against Gram-positive bacteria and behaved as bactericidal agents. The spatial disposition of the active groups seems to play a key role, with the highest activity observed for a C3v geometry. The presence of quaternary ammonium functional groups also facilitated the internalization of the molecules into the bacteria. Levels of cytotoxicity similar to that of the solvent were obtained for most compounds against COS-1 and VERO cells.